Indigenous Microbial Biostimulation for Microbial Enhanced Oil Recovery through Oil Degradation with Variation in Nutrent Concentrations - Handaruni, Rika; Astuti, Dea Indriani; Purwasena, Isty Adhitya; Afifah, Lulu Nur (UI Scholars Hub, 2020)
Oil production in Indonesia has been declining since 2002, and this decline is incompatible with the high oil consumption in Indonesia. As such oil production in Indonesia should be improved. Biostimulation in microbial enhanced oil recovery involves environmental modification to stimulate microbial growth within a reservoir by adding limiting nutrients. Variation in C, N, and P concentrations injected to reservoirs can induce different responses from indigenous microbes and increase oil recovery. In this study, molasses, urea and diammonium phosphate were used as nutrients injected to a reservoir for biostimulation. Biological, physical and chemical characteristics after biostimulation were observed and bacterial growth was monitored up to 42 days. The physical characteristics observed were pH, oil viscosity, and interfacial tension. Gas chromatography mass spectrometry was performed to determine the chemical characteristics of oil. Results showed that the addition of nutrients at various concentrations yielded different production patterns of metabolites. The addition of urea and diammonium phosphate induced biosurfactants overproduction and increase hydrocarbon degradation of by bacteria. Therefore, hydrocarbons were degraded for the first 14 days, and polymerized again on days 14 to 42.